A clinical and biochemical study of dengue fever in Kosi region of Bihar, India - Kumar, Rakesh; Suman, Shanker; Ranjan, Rajiv (International Journal of Advances in Medicine, 2017)
Background: Dengue is a debilitating arthropod-borne viral (arboviral) disease in humans. To improve diagnostics for patients with dengue so that they can receive effective treatments at earliest. In addition, a better understanding of clinical and biochemical study of dengue cases, effective measures can be aimed for the prevention and control of dengue epidemics. Methods: A retrospective clinical and laboratory study was undertaken among admitted patients in the Department of Physiology at Katihar Medical College and Hospital, Katihar, Kosi region of Bihar, India. Forty-two (42) patients admitted over a period of two years, with laboratory results for NS1 antigen and or /IgM positive, for dengue fever, were taken in the study. Clinical features, haematological and biochemical parameters were noted. Results: Out of the 42 patients, 38 patients were male (90.4%) and 4 patients were female (9.6%). Pyrexia was the major symptom (100%) followed by splitting headache (90.40%), myalgia (76.19%), conjunctival redness (50.00%), skin rash (42.80%), abdominal pain (30.95%), hepatosplenomegaly (28.57) ascites (26.19%) and retro orbital pain (19.04%). Severe thrombocytopenia (69.51%), leukopenia (20.19%) and elevated serum SGOT and SGPT (88.54%) were observed. Conclusions: Dengue infection is increasing proportional to increased urbanization and compromised sanitation measures. Fever associated with headache, retro orbital pain, erythematous morbilliform rash, conjunctival redness and itching in palms and soles along with thrombocytopenia, leukopenia, elevated SGPT should prompt a clinician on the possibility of dengue infection.